Regional Delivery of Anti-PD-1 Agent for Colorectal Liver Metastases Improves Therapeutic Index and Anti-Tumor Activity - Chai, Louis F.; Hardaway, John C.; Heatherton, Kara R.; O’Connell, Kyle P.; Lopes, Mikayla C.; Rabinowitz, Benjamin A.; Ghosh, Chandra C.; Guha, Prajna; Jaroch, David; Cox, Bryan F.; Katz, Steven C. (Vaccines (Basel), 2021)
Metastatic liver tumors have presented challenges with the use of checkpoint inhibitors (CPIs), with only limited success. We hypothesize that regional delivery (RD) of CPIs can improve activity in the liver and minimize systemic exposure, thereby reducing immune-related adverse events (irAE). Using a murine model of colorectal cancer liver metastases (LM), we confirmed high levels of PD-L1 expression on the tumor cells and liver myeloid-derived suppressor cells (L-MDSC). In vivo, we detected improved LM response at 3 mg/kg on PTD7 via portal vein (PV) regional delivery as compared to 3 mg/kg via tail vein (TV) systemic delivery (p = 0.04). The minimal effective dose at PTD7 was 5 mg/kg (p = 0.01) via TV and 0.3 mg/kg (p = 0.02) via PV. We detected 6.7-fold lower circulating CPI antibody levels in the serum using the 0.3 mg/kg PV treatment compared to the 5 mg/kg TV cohort (p < 0.001) without increased liver toxicity. Additionally, 3 mg/kg PV treatment resulted in increased tumor cell apoptotic signaling compared to 5 mg/kg TV (p < 0.05). Therefore, RD of an anti-PD-1 CPI therapy for CRCLM may improve the therapeutic index by reducing the total dose required and limiting the systemic exposure. These advantages could expand CPI indications for liver tumors.